2015
DOI: 10.1073/pnas.1520638113
|View full text |Cite
|
Sign up to set email alerts
|

CAMSAP3 orients the apical-to-basal polarity of microtubule arrays in epithelial cells

Abstract: Polarized epithelial cells exhibit a characteristic array of microtubules that are oriented along the apicobasal axis of the cells. The minus-ends of these microtubules face apically, and the plus-ends face toward the basal side. The mechanisms underlying this epithelial-specific microtubule assembly remain unresolved, however. Here, using mouse intestinal cells and human Caco-2 cells, we show that the microtubule minus-end binding protein CAMSAP3 (calmodulin-regulated–spectrin-associated protein 3) plays a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
171
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(184 citation statements)
references
References 37 publications
11
171
0
Order By: Relevance
“…1A). In agreement with previous publications (Meng et al, 2008;Tanaka et al, 2012;Toya et al, 2016), in this cell line, CAMSAP3-GFP localized to microtubule ends, colocalized with endogenous CAMSAP2 and was concentrated at the apical side of polarized Caco-2 monolayers ( Fig. 1B-D).…”
Section: Visualization Of Localization and Dynamics Of Camsap3 In Polsupporting
confidence: 93%
See 4 more Smart Citations
“…1A). In agreement with previous publications (Meng et al, 2008;Tanaka et al, 2012;Toya et al, 2016), in this cell line, CAMSAP3-GFP localized to microtubule ends, colocalized with endogenous CAMSAP2 and was concentrated at the apical side of polarized Caco-2 monolayers ( Fig. 1B-D).…”
Section: Visualization Of Localization and Dynamics Of Camsap3 In Polsupporting
confidence: 93%
“…Intestinal epithelial cells of those mice could still polarize and form a normal brush border, in spite of the fact that the microtubules were disorganized, and the nuclei and Golgi membranes mispositioned (Toya et al, 2016). Experiments in Caco-2 cells, a human intestinal cancer cell line, have demonstrated that the first coiled-coil region of CAMSAP3 is involved in recruitment of CAMSAP3-bound microtubule minus ends to the apical side (Toya et al, 2016). In CAMSAP1, this coiled-coil region was shown to bind to spectrin (King et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations